Implementação da estratégia de prevenção combinada do HIV/AIDS em serviços de atenção especializada - Rocha, Rômulo do Nascimento (2024)
HIV/AIDS still remains a worrying public health problem. Various alternatives in the field of prevention, surveillance, control and treatment have made Brazil a world reference in its response to the epidemic. However, there are still difficulties in finding effective preventive responses to the dynamic nature of the epidemic, which is characterized as both viral and social and requires a simultaneous approach of behavioral, structural and biomedical alternatives to prevent exposure to the virus. This study analyzes the implementation of the Combined HIV Prevention Strategy in Specialized Care Services (SAE) in the municipality of Fortaleza. The specific objectives are: 1) To identify HIV prevention approaches and actions in specialized care services (SAE); 2) To characterize implementation taking into account interactions, conditions and work structures for Combined HIV Prevention; and 3) To examine effects and gaps in implementation in health services from the perspective of health professionals. This is an analysis of the implementation of bottom-up public policies, particularly from the perspective ofstreet-level bureaucrats, which includes the investigation of the empirical performance of actors who implement policies in close relationship with users. Five Specialized Care Services (SAE) in the municipality of Fortaleza were selected. Secondary data was analyzed. 16 semi-structured interviews were conducted with professionals who work directly with HIV/AIDS prevention. The study identified different organizational arrangements and heterogeneity in the types of HIV prevention strategies in the services. Biomedical approaches to prevention still prevail, although there is a perceived need for other alternatives. There were gaps in the composition of multi-professional teams, multiple organizational flows within the SAEs, and formal and informal links between services in the network to guarantee a line of HIV care, even in the context of limitations. Problems of structure and workforce influence the provision of the strategies set out in Combined Prevention. We also found mechanisms and discretionary decisions by health professionals that are made based on a categorization of users and influence the implementation process. There is a gap between the formulation and implementation of the Combined HIV Prevention proposal.